Numerical Investigation of Inlet Thermodynamic Conditions on Solid Fuel Ramjet Performances - Weixuan Li; Dan Zhao; Xiong Chen; Liang Zhu; Siliang Ni (International Journal of Aerospace Engineering)
In this work, 2D numerical RANS (Reynolds Average Navier-Stokes) simulations were carried out to investigate the thermodynamic performance of a solid fuel ramjet (SFRJ) with different inlet conditions. This is achieved by using an in-house FORTRAN code to simulate a 2D turbulent, reacting, unsteady flow in the ramjet engine. The inlet conditions are characterized by three key parameters: (1) swirl number (SN), (2) mass flow rate (ṁair), and (3) inlet temperature (Tin). With the code numerically validated by benchmarking with a number of computed cases, it is applied to perform systematic studies on the turbulent flow recirculation, combustion, and heat transfer characteristics. It is found that increasing SN, ṁair, or Tin can dramatically enhance the combustion heat release rate, regression rate, and combustor average temperature. Furthermore, the analysis on the chemical reaction intermediate (CO) reveals that the chemical reaction is more sufficient with increased ṁair, but SN=0. In addition, a secondary vortex is generated at the corner of the backward facing step in the presence of a swirl flow resulting from the instability of the shear layer. Finally, the nonlinear correlations between the heat transfer, combustion characteristics, and flow field characteristics and the corresponding inlet thermodynamic parameters are identified.